Fatores associados à prevalência da infecção por HIV no Haiti em mulheres em idade fértil : análise do inquérito nacional sobre morbidade, mortalidade e uso de serviço de 2016-2017 - Thimothée, Yves Sanley (2022)
According to the World Health Organization, about 19.3 million women have been diagnosed with the HIV virus worldwide as of July 2021. In Haiti, about 86,000 women aged 15 to 49 are living with HIV. Also in the Haitian context, in 2020, there is a higher prevalence rate of infection in women (2.3%) than in men (1.6%), indicating that they are more vulnerable to infection and factors associated with the prevalence of HIV infection. However, there are few population studies on factors associated with HIV, especially in Haitian women of childbearing age. Thus, it is questioned whether there is an association between sociodemographic and sexual behavior factors and the prevalence of HIV infection in Haitian women of childbearing age. Objective – Analyze the prevalence of HIV infection and factors associated with HIV infection in Haitian women of reproductive age between 2016 and 2017. Methods - This is a cross-sectional observational study, in which data from the sixth survey on mortality, morbidity and use of services (EMMUS VI) in Haiti were analyzed. These are data referring to 9,698 women of childbearing age, interviewed and tested for HIV between 2016 and 2017. To identify the sociodemographic and sexual behavior factors associated with the prevalence of HIV infection, simple and multiple logistic regression was performed to estimate the Odds Ratio (OR) and their respective 95% confidence intervals. Variables with a value of p<0.20 in the simple logistic regression were included in the multiple model, being maintained those with a significance level < 0.05. The backward method was used to eliminate the variables with the highest p-value from the initial model. Results - In the period studied, 218 women were infected with HIV (2.25%). Statistically significant associations were identified between HIV seropositivity for older age, separation and/or divorce, lower level of education, practice of voodoo religion, and multiple sexual partners throughout life. Conclusions - These findings indicate the need for effective measures in the control and prevention of HIV infection among Haitian women of childbearing age and are part of the specific categories.